2019
DOI: 10.1038/s41467-019-11227-4
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1 and PKB/Akt control the muscle response to denervation by regulating autophagy and HDAC4

Abstract: Loss of innervation of skeletal muscle is a determinant event in several muscle diseases. Although several effectors have been identified, the pathways controlling the integrated muscle response to denervation remain largely unknown. Here, we demonstrate that PKB/Akt and mTORC1 play important roles in regulating muscle homeostasis and maintaining neuromuscular endplates after nerve injury. To allow dynamic changes in autophagy, mTORC1 activation must be tightly balanced following denervation. Acutely activatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
104
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(115 citation statements)
references
References 59 publications
10
104
1
Order By: Relevance
“…These cells represent less than 20% of the muscle tissue but they are sufficiently represented to generate detectable expression of inactivated genes in muscle extracts. This is true for H2A.Z dKO muscles and for all muscle specific inactivation of ubiquitously expressed genes [38][39][40][41][42] . By allowing to visualize individual nuclei, immunofluorescence was therefore the best way to evaluate the efficiency of H2A.Z knock-down in muscle fibers.…”
Section: Discussionmentioning
confidence: 85%
“…These cells represent less than 20% of the muscle tissue but they are sufficiently represented to generate detectable expression of inactivated genes in muscle extracts. This is true for H2A.Z dKO muscles and for all muscle specific inactivation of ubiquitously expressed genes [38][39][40][41][42] . By allowing to visualize individual nuclei, immunofluorescence was therefore the best way to evaluate the efficiency of H2A.Z knock-down in muscle fibers.…”
Section: Discussionmentioning
confidence: 85%
“…In support of this notion, a recent study revealed that denervation-induced alterations in Ca 2+ signaling in muscle signals HDAC4 to shuttle between the nucleus and cytoplasm. HDAC4 has been shown to promote MuSC proliferation (Marroncelli et al, 2018) and co-localize with sub-synaptic myonuclei after denervation (Castets et al, 2019). Whether similar Ca 2+ -mediated mechanisms of myogenesis modulate MuSCs after denervation is unclear, but the calmodulin (CaM)-dependent kinase (CaMK), which prevents the formation of HDAC-myocyte enhancer factor 2 (HDAC-MEF2) complexes, releases MEF2 from HDAC4 and HDAC5 and promotes myogenic transcriptional activity in response to Ca 2+ activity.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we unveil a determinant function of obestatin signaling in neuromuscular integrity that allow to regulate muscle homeostasis via speci c activation of the Akt-mTORC1 axis. Although mTORC1 becomes activated in control muscle, constant activation of mTORC1 triggers feedback inhibition of Akt [80]. This fact determines a key difference between groups that establishes the activity of the ubiquitin/proteasome system by regulation of E3 ubiquitin-ligases under the control of HDAC4/myogenin and FoxO transcription factors [80][81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%
“…Although mTORC1 becomes activated in control muscle, constant activation of mTORC1 triggers feedback inhibition of Akt [80]. This fact determines a key difference between groups that establishes the activity of the ubiquitin/proteasome system by regulation of E3 ubiquitin-ligases under the control of HDAC4/myogenin and FoxO transcription factors [80][81][82][83][84]. Interestingly, the activation of S6 alone, or lack of mTOR signaling to 4E-BP1 only, is not su cient to increase muscle mass in control muscle.…”
Section: Discussionmentioning
confidence: 99%